Management of pressure ulcers: Advanced Healing. Abel Gilbert Pontón Hospital (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
Bedsores, decubitus ulcer or pressure ulcer, are skin lesions, which can reach the subcutaneous cell or muscle caused by pressure, friction, prolonged friction, usually on a bony prominence. The most frequent sites of appearance are the surfaces that cover bony parts (bony prominence) such as the sacrum, trochanters, ankle, heels, etc. It is a coordinated clinical-surgical management, with extensive collaboration from the nursing professional. In the management of pressure ulcers, the following should be considered: Risk assessment according to the chosen scale, assessment of the presence of the lesion and staging, initial classification according to stages, description of the pressure ulcer, pressure relief on surfaces bone, postural changes, anti-decubitus measures, avoid humidity or excess heat, good nutritional support. The treatment of pressure ulcers will depend on the degree, in our study carried out at the Abel Gilbert Pontón hospital, by the advanced healing team, we found that 183 patients required surgical debridement of necrotic tissues (grade 3 and 4) with use in addition to continuous wet dressings, 380 patients required only healing with the use of wet dressings.
Keywords: debridement; wet dressin; hydrogel; hydrocolloids